Air pollution monitoring system using LoRa modul as transceiver system - Mia Rosmiati; Moch. Fachru Rizal; Fitri Susanti; Gilang Fahreza Alfisyahrin (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Air pollution is a disaster that can indirectly interfere with human health, Indonesia is the third highest country in the world that has pollution levels, one of the types of pollution that threatens public health is the increase of CO, NO2 and SO2 level in the air. With the increasing level of air pollution in the city, it requires a device that can monitor air pollution in a real time. By integrating air sensor and Raspberry Pi as data processor and using LoRa module as transceiver module, then the process of transmitting data from transmitter to receiver can be done directly without connected internet. In a test, the system can transmit intensity data information by wireless system on Line Of Sight (LOS) scemes at a maximum distance of 1.7 Km and Non Line Of Sight (NLOS) scheme at a distance of 400 meters with a average delay is 2 second.